PERSPECTIVE OF PROSPECTIVE PRIMARY SCHOOL TEACHERS ON ALTERNATIVE EVALUATION - Ali KOLOMUÇ (Fırat University, 2019)
This study was conducted to discover prospective primary school teachers’ frequency of usage, efficacy level about alternative evaluation. The questionnaire developed by Okur (2009) was arranged and carried out on the prospective primary school teachers by the researchers. The data instrument employed in the study consists of three chapters. At the first chapter, there are four items about the prospective teachers’ personal information and 21 items about the measurement and assessment techniques consisting of 21 methods which they will use. At the second chapter, there are two items to define prospective teachers’ efficacy and frequency to use the alternative measurement and assessment techniques. At the third chapter there are 32 items about the prospective teachers’ attitudes towards using the alternative measurement and assessment techniques. The results from the study was compared to the results in the literature. The research sample consisted of the prospective primary school teachers studying at the Artvin Coruh University. Opinions of prospective primary school teachers on the alternative evaluation was collected through semi-structured interview. The findings on whether frequency of usage the alternative evaluation techniques varied or not, was analysed through SPSS 15. In the data analysis frequency, t-test and variance analysis was employed. Based on the results from the present study it was predicted that what extent they will use the alternative evaluation techniques in the future.